(3JGQjN GdNdaGA (B/s - (3GdLdGd GdSjhWj, YHO GdQMef Hf CHj HcQ Hf eMeOs 849-911 (3gLQjs; (3OGQ GdefgGL ddfTQ hGdJhRjY (B((3LOI, GdSYhOjI(B).s (3eQcR GdOQGSGJ hGdJMbjb GdYdej(B.s (3GddLfI GdYdejIs ((3OGQ GdefgGL ddfTQ hGdJhRjY ,s, 2019)
(3cJGH JGQjNj hgh eNJUQ hgh jJVef aJQI ef HOGjI GdNdGaI Edi fgGjI GdYUQ GdYHGSj JHfi GdSjhWj aj gPG GdcJGH QhGjI Cgd GdSfI hGdLeGYI YeheG aj JUfja GdNdaGA hGdNdGaI hjYJeO aj QhGjJg Ydi cJH cHGQ GdeDQNjf YfO Cgd GdSfI hYdi QCSge GHf cKjQ hGdPgHj(B. (3aGdcGJH UGMH fXQI eQcRjI ddYGde GdESdGej hGdJj JJeKd aj GdGYJQGa HGdNdaGA GdQGTjOjf aj GdeOjfI hGdchaI hGdCehjjf aj GdTGe hGdYHGSjjf aj HZOGO hSGeQGA hGdbGgQI hgh ePgH eYXe Cgd GdTQb GdChSW(B.s
(3PcQ Ydi GdZdGa (B: (3GdWHYI GdaQjOI GdJj GYJeOJ Ydi SJ fSN NWjI GKfJGf efgG fSNJG ef fSNI JdejP GdEeGe GdSjhWj(B.s
(3HHdjhLQGajI (B: (3UaMI (B811-838.s
Keywords: (3GdNdaGA GdQGTOhfs -- (3JGQjNs; (3GdJGQjN GdESdGejs -- (3YUQ UOQ GdESdGes; (3GdNdaGA GdQGTOhfs -- (3JQGLes